Sociodemographic characteristics help predict Canadian urbanites’ acceptability of restaurant food environment policies - Lambert-De Francesch, Jessica; Saint-Onge, Kadia; Muhajarine, Nazeem; Gauvin, Lise (Frontiers in Nutrition, 2024)
Public acceptability of policies aiming to improve the healthfulness of the restaurant food environment is key to their successful implementation. Yet, the acceptability of these policies remains ambiguous, especially across diverse population groups. This study aims to examine associations between sociodemographic characteristics and acceptability levels of three restaurant food environment policies of varying degrees of intrusiveness across 17 urban Canadian jurisdictions. Data was extracted from the THEPA survey, one of the largest and most jurisdictionally comprehensive surveys on intervention acceptability (N=27,162). To account for potential jurisdictional differences in acceptability, for each policy, multilevel logistic regression models were developed. Results indicated that, on average, those in complete agreement with the implementation of the targeted policies represented 20.3%-26.9% of participants, depending on the policy. Acceptability varied according to policy intrusiveness, jurisdiction, and participants' sociodemographic characteristics. Women, individuals with household incomes of <$40,000/year, immigrants from a high-income country other than Canada, and Indigenous peoples were more likely to express complete agreement with all policies, versus men, participants with household incomes of $40,000-$79,999/year, Canadian-born individuals, and non-Indigenous individuals. A lower likelihood of expressing complete agreement with all policies was observed for those with a $80,000-$119,999/year household income, versus those with a $40,000-$79,999/year household income. For selected policies and models, other sociodemographic characteristics (i.e., age, education, and being born in a low-or middle-income country) predicted acceptability. The examined sociodemographic characteristics did not explain jurisdictional differences in acceptability. Understanding jurisdictional differences in acceptability merits further research. Policy implications involve engaging diverse sociodemographic groups in conversations about acceptable ways in which their restaurant food environment could be rendered more healthful.